2012
DOI: 10.1016/j.clim.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor alpha modulates toll-like receptor signaling in murine lupus

Abstract: Systemic lupus erythematosus (SLE) is a disease that disproportionately affects females. Despite significant research effort, the mechanisms underlying the female predominance in this disease are largely unknown. Previously, we showed that estrogen receptor alpha knockout (ERαKO) lupus prone female mice had significantly less pathologic renal disease and proteinuria, and significantly prolonged survival. Since autoantibody levels and number and percentage of B/T cells were not significantly impacted by ERα gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 43 publications
(42 reference statements)
4
43
0
Order By: Relevance
“…However, ERα also acts via multiple non-classical signaling pathways to regulate cellular responses. Cunningham et al reported that ERα regulates TLRinduced inflammation in a ligand-independent manner [11,14,32]. Here, we have shown that ERα, upregulated by RNA virus infection, functions as an adaptor protein and negatively regulates the RLRtriggered IRF3 activation and type I interferon production.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…However, ERα also acts via multiple non-classical signaling pathways to regulate cellular responses. Cunningham et al reported that ERα regulates TLRinduced inflammation in a ligand-independent manner [11,14,32]. Here, we have shown that ERα, upregulated by RNA virus infection, functions as an adaptor protein and negatively regulates the RLRtriggered IRF3 activation and type I interferon production.…”
Section: Discussionsupporting
confidence: 49%
“…These findings indicate that ERα may not act via the classical ligand-dependent signal in the immune system. The regulation of ERα in immune response may act via the non-classical ligand-independent mechanisms and suggests that the immune effects of estrogen and ERα can be separated from hormonal effects [11,14]. However, the role of ERα in innate immune response and their crosstalk with the RIG-I pathway in antiviral innate response is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…While a limited number of genes are known to be regulated by estrogen at present, recent evidence suggests that this list is likely much larger [2]. In lupus mouse models, studies have shown enhanced survival and decreased disease severity with ERα deficiency, while no effect was observed with regard to ERβ [3, 4]; thus supporting other studies also indicating the important role of the ERα receptor subtype in promoting autoimmune-mediated inflammation [5]. Additionally, we have previously identified a novel ERE proximal to the toll-like receptor (TLR)8 genetic locus and, using peripheral blood mononuclear cells (PBMCs) derived from systemic lupus erythematosus (SLE) patients and healthy controls, demonstrated both elevated expression of TLR8 in SLE and significant ERα-dependent induction with estrogen treatment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we have previously identified a novel ERE proximal to the toll-like receptor (TLR)8 genetic locus and, using peripheral blood mononuclear cells (PBMCs) derived from systemic lupus erythematosus (SLE) patients and healthy controls, demonstrated both elevated expression of TLR8 in SLE and significant ERα-dependent induction with estrogen treatment [6]. Furthermore, stimulation of leukocytes from ERα deficient, lupus-prone mice with TLR agonists has been shown to elicit a significantly reduced inflammatory response [4]. Collectively, these data indicate an association between ERα-mediated TLR activation following estrogen stimulation and suggest that this pathway may be involved pathologically in SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen synergizes with type I IFN to increase expression of TLRs and to decrease expression of another inhibitory coreceptor of the BCR, FcγRIIB [118][119][120]. One study of estrogen receptor α (ERα)-deficient NZB/W mice suggests that the absence of ERα diminishes renal diseases but does not alter autoantibody titer [121]. Other studies show that effects of estrogen on B cells are mediated through ERα, and that an absence of ERα prevents an estrogen-mediated breach of B cell tolerance [122].…”
Section: Gender Influencesmentioning
confidence: 99%